Public Health Service Research in Guatemala: Toward New Scholarship - Spector-Bagdady, Kayte (The Hastings Center report, 2013)
A commentary on “‘Ever Vigilant’ in ‘Ethically Impossible’: Structural Injustice and Responsibility in PHS Research in Guatemala,” from the May-June 2013 issue.